Strategi pemberdayaan masyarakat Desa Tanjung Belit di sekitar Suaka Margasatwa Bukit Rimbang Bukit Baling Kabupaten Kampar Provinsi Riau - Bastianto Bastianto; Sukendi Sukendi; Nofrizal Nofrizal (Jurnal Zona, 2019)
One of the problems faced in the management of conservation areas, including wildlife reserves, is the community activities in and around the area to meet their daily needs. They in general have traditionally carried on their traditional lives and most of them live at a very subsistence economic level. Therefore the success of the management of conservation areas including wildlife reserves is very dependent on the attitudes and support of the community both at the local and national level. Bukit Rimbang Bukit Baling Wildlife Reserve has been determined by the Government of the Republic of Indonesia through the Decree of the Minister of Forestry number SK.3977/Menhut-VII/KUH/2014 on May 23, 2014 with an area of 141,226.25 hectares (BBKSDA Riau, 2015). Tanjung Belit Village, Kampar Kiri Hulu Subdistrict, Kampar Regency is one of the villages bordering the Bukit Rimbang Hill Baling High School which has high public concern for the preservation of the forest, rivers and the surrounding environment. The people of Tanjung Belit Village have traditionally used natural resources in and around the Bukit Rimbang Bukit Baling Wildlife Reserve area to fulfill their daily needs by farming / gardening and collecting forest products and other river products. However, the availability of these forest and river resources, if taken continuously, will certainly decrease both in quality and quantity. While the necessities of life always increase along with the increasing population and the progress of the times. Therefore efforts should be made to the community and natural resources, so that the availability of natural resources and the necessities of life can be improved. This study aims to analyze the socio-economic conditions of the people of Tanjung Belit Village, identify the potential of Bukit Rimbang Bukit Baling Wildlife Reserve, formulate the Tanjung Belit Village community empowerment strategy around the Bukit Rimbang Bukit Baling Wildlife Reserve, Kampar Regency, Riau Province. The research approach used in this study is a quantitative approach to the survey method.he results showed the socio-economic conditions of the people of Tanjung Belit Village were still classified as poor and less skilled. However, local wisdom and a strong will to try to be a social capital in community empowerment. The potential of Bukit Rimbang Hill Bukit Baling has quite high potential from flora, fauna and nature tourism, but for the development of agricultural business is still limited due to the status of the wildlife reserve. The results of the study can be formulated a strategy of community empowerment in the village of Tanjung Belit around Bukit Rimbang Bukit Baling Wildlife Reserve; (a) optimize land use in agricultural business development; (b) encourage training activities to improve human resources in the context of community empowerment; (c) active community involvement in the management of the Bukit Rimbang Bukit Baling Wildlife Reserve area; (d) increasing cooperation support between the government and stakeholders in developing infrastructure supporting natural tourism around the Bukit Rimbang Bukit Baling Wildlife Reserve.